2023
DOI: 10.1177/00219983221150046
|View full text |Cite
|
Sign up to set email alerts
|

Development and verification of a cure-dependent visco-thermo-elastic simulation model for predicting the process-induced surface waviness of continuous fiber reinforced thermosets

Abstract: Process-induced surface waviness effects represent a major concern for series production of high-quality lightweight structures based on fiber reinforced plastics (FRP). This paper suggests a method for the numerical prediction of these effects by using the example of processing glass fiber reinforced plastics (GFRP) in a resin transfer molding (RTM) process. The influence of reaction kinetics, chemical shrinkage and cure-dependent viscoelastic properties of the resin are taken into account. Furthermore, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Due to this, the roughness before any post-processing treatment is of great concern, especially in the case of thermoset matrix composites manufactured via AM, due to amorphous polymerization. The roughness simulation for continuous GF and bisphenol photosensitive (Lorenz et al, 2022) [113]. The model was developed in TexGen software 3.13.1, with experimental material properties.…”
Section: Surface Roughness Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this, the roughness before any post-processing treatment is of great concern, especially in the case of thermoset matrix composites manufactured via AM, due to amorphous polymerization. The roughness simulation for continuous GF and bisphenol photosensitive (Lorenz et al, 2022) [113]. The model was developed in TexGen software 3.13.1, with experimental material properties.…”
Section: Surface Roughness Simulationmentioning
confidence: 99%
“…polymerization. The roughness simulation for continuous GF and bisphenol photosensitive (Lorenz et al 2022) [113] The model was developed in TexGen software, with experimental material properties. The model was developed for two directions, with mean profiles and extremum values, as shown in Figure 56 .…”
Section: Surface Roughness Simulationmentioning
confidence: 99%
“…Lorenz et al [17] suggested a method for the numerical prediction of surface waviness effects on glass fiber reinforced plastics (GFRP) in a resin transfer molding (RTM) process. They revealed that simulations and experiments agreed satisfactorily and observed surface waviness significantly influenced by the curing temperature rather than the analyzed neat resin layer thickness.…”
mentioning
confidence: 99%